Effects of Shigella flexneri Exposure on Fluid Secretion and Histopathological Changes in Mouse Ileum and Colon - Endang Ulupi Khoirunnisa; Sumarno Reto Prawiro; Habiba Aurora (FORIKES, 2026)
Diarrheal disease remains one of the leading causes of mortality worldwide, and in Indonesia Shigella flexneri constitutes a major etiological agent of endemic diarrhea. The clinical manifestations range from watery diarrhea to bacillary dysentery, or a combination of both, reflecting the bacterium’s biphasic pathogenic mechanisms. However, the specific processes by which S. flexneri induces watery diarrhea have not been fully elucidated. This study aimed to compare intestinal fluid secretion and histopathological alterations in the ileum and colon of mice, thereby contributing to a deeper understanding of Shigella pathogenesis. Four experimental groups were examined: negative control ileum, ileum exposed to S. flexneri, negative control colon, and colon exposed to S. flexneri. Using the ex vivo Mice Ligated Ileal Loop (MLIL) method, intestinal segments were incubated for 30 minutes, and intestinal weight was recorded at 5‑minute intervals. Data were analyzed using an unpaired t‑test, while histological findings served as supplementary qualitative evidence. The results demonstrated a greater increase in intestinal weight in the S. flexneri–exposed groups compared with controls, although the differences did not reach statistical significance. Histological evaluation was limited due to tissue autolysis, which hindered optimal interpretation. In conclusion, exposure to S. flexneri tended to enhance intestinal fluid secretion, particularly in the colon at the 30‑minute mark; however, this effect was not statistically significant under short‑term ex vivo conditions. Longer incubation periods and improved tissue preservation techniques are required to more accurately capture the full pathogenic effects of S. flexneri.Keywords: Mice Ligated Ileal Loop (MLIL); Shigella flexneri; intestinal fluid secretion; ex vivo